Effects of Excessive Grazing of Livestock on Soil Organic Carbon Changes in Kermanshah Province - Mohammad Gheitury; Mosayeb Heshmati; Yahya Parvizi; Mohsen Abbasini (جغرافیا و پایداری محیط)
Excessive grazing of livestock is an important parameter in degradation of vegetationand soil erosion in rangeland. The purpose of this study was to investigate the effect of trapping on Organic carbon storage of soil. The research was carried out in three regions: Einal Kosh, Siyah Kamar and Sarfiroz Abad in Kermanshah province. Soil characteristics, vegetation cover and management were measured by field operations in three sampling areas. Soil sampling was done in 0-20 depths. Besides, a total 24 soil samples were taken in rangeland extreme grazing. Soil samples were air dried and sieved through 2 mm mesh and analyzed in the soil laboratory. Soil samples were taken from 0-20 cm depth for routine soil analysis including texture, calcium carbonate, pH, EC, and soil organic carbon as well as soil aggregate size distribution. Statistical analysis of data showed that the average organic carbon of protected rangelands (12.3%) was about 2% higher than that of extreme grazing (16.1 %) rangelands. Therefore, unsuitable management of the rangelands leads to soil degradation by reducing organic carbon and also changing the size of the aggregate, which results in soil sensitivity to erosion.